The Value of Pre-Islamic Poetry in Ibn Abd Rabbuh’s “Aleqd” and his Poetry - Ghidan, Jamal Ali (Journal of Arabic Language Sciences and Literature, 2024)
This research aims to detail arguments about the value of pre-Islamic poetry of Ibn Abd Rabbo’s book “Aleqd” and in his own poetry, which comprises an introduction and eleven themes. The researcher has followed the descriptive analytical approach by tracing the topics of such themes in the sources and references, and in “Aleqd” and the poetry of Ibn Abd Rabbo himself. Among the questions raised in this research are: What is the extent of Ibn Abd Rabbo’s interest in pre-Islamic poetry in “Aleqd” and poetry? In his “Aleqd” and poetry, the research concluded that Ibn Abd Rabbo draws on the pre-Islamic poetry, which has been the basis for Arabic poetry throughout the ages, in terms of its structures, methods, and most meanings indicated. The researcher recommends identifying the ways in which Ibn Abd Rabbo contradicted pre-Islamic poetry, and studying the methods adopted by Ibn Abd Rabbo in his opposition to pre-Islamic poetry in Ibn Shahid’s poetry and letters. He also recommends studying the prosodic rhymes or couplets created by Ibn Abd Rabbo in the Arabic prosody, and pinpointing the extent to which he was influenced by pre-Islamic poetry. Additionally, he also recommends touching upon the ways of Ibn Abd Rabbo in explaining Arabic poetry and correcting its meanings based on the news and poetry of the pre-Islamic era as well as assessing the method adopted by Ibn Bassam Al-Shantarini in his criticism of pre-Islamic poetry. Finally, he recommends studying Ibn Abd Rabbo’s criteria followed when criticizing the pre-Islamic poetry and his views on citation and being influenced by his predecessors in terms of poetry and prose.